Distribution and hybridization between Culex pipiens and Culex quinquefasciatus (Diptera: Culicidae) in Argentina - Walter R. Almirón; Silvia G. Humeres; Cristina N. Gardenal (Memorias do Instituto Oswaldo Cruz, 1995)
To better undesrtand the distribution of Culex pipiens and Cx. quinquefasciatus in Argentina, samples were collected from six localities situated in a North-South line from Castelli (Chaco Province) to Puerto Madryn (Chubut Province). Identification was based on the morphology of male genitalia. Only Cx. quinquefasciatus was found in Castelli and Esperanza, while in Rosario, 95.3% belonged to this species and 4.7% represented hybrid forms. Southern samples included only Cx. pipiens. With the purpose of verfying if Cx. pipiens and Cx. quinquefasciatus hybridize, different crosses between the two species were perfomed. All crosses produced viable egg rafts. Hatching ranged from 70 to 100%, except in one cross, female Cx. pipiens x male Cx. quinquefasciatus, where a high incompatibility was observed (11.1%hatch). The F1 hybrids obtained all crosses were fertile. The finding of hybrid forms in nature can be interpreted as evidence for subspecific status of Cx. pipiens and Cx. quinquefasciatus in Argentina.